Computational systems pharmacology reveals an antiplatelet and neuroprotective mechanism of Deng-Zhan-Xi-Xin injection in the treatment of ischemic stroke. (September 2019) - Zhao, Jing; Lv, Chao; Wu, Qiuling; Zeng, Huawu; Guo, Xin; Yang, Jian; Tian, Saisai; Zhang, Weidong
Graphical abstract: Abstract: Herbs are typically prescribed in traditional Chinese medicine (TCM) to treat complex diseases. The multicomponent nature of herbal drug ingredients makes it difficult to readily understand their mode of action. To decipher their molecular mechanisms, here we proposed a novel computational systems pharmacology based approach, which consisted of transcriptome profiling, data collection, statistical analysis, network algorithm, bioinformatics analysis and pharmacological validation. The network algorithm called signed random walk with restart (SRWR) was used to simulate the propagation of drugs' effects on networks. This algorithm could identify proteins either positively or negatively regulated (activated or inhibited) by drugs on human signaling networks. To establish proof of principle, the herbal product Deng-Zhan-Xi-Xin injection (DZXXI), which exhibits pharmacological effects in ischemic stroke but its mechanism was unclear, was analyzed. Eighty-three targets were predicted with high confidence for DZXXI's active compounds in plasma, and 87 differentially expressed genes (DEGs) were identified in MCF7 cells treated with DZXXI. These target genes were further found to be associated with pathways involved in neuronal apoptosis in ischemic stroke, such as NF-κB signaling, TNF signaling, and PI3K-Akt signaling. Intersection analysis between DZXXI's putative targets with ischemic stroke-associated genes identified two important targets ( PTGS1, PTGS2 ) corresponding to four DZXXI compounds, which were further validated using in silico and in vitro/vivo models. The most inhibited genes identified by the SRWR algorithm were significantly enriched with ischemic stroke-associated disease genes, antiplatelet associated pathways, and their encoded proteins were enriched in brain, vascular endothelium and platelets. The CMAP analysis based on DEGs suggested that DZXXI could function as both an anti-inflammatory and anti-platelet agent. Taken together, the computational analysis suggested that DZXXI exhibited anti-platelet and neuroprotective effects in the treatment of ischemic stroke. These deductions were preliminarily confirmed by subsequent in vitro / vivo studies. This approach provides a systems perspective to study the relevance between herbal drugs and disease processes, and can reveal possible pharmacological effects of multiple ingredients within herbal product.